Solving Fokker-Planck Equations on Cantor Sets Using Local Fractional Decomposition Method - Shao-Hong Yan; Xiao-Hong Chen; Gong-Nan Xie; Carlo Cattani; Xiao-Jun Yang (Abstract and Applied Analysis)
The local fractional decomposition method is applied to approximate the solutions for Fokker-Planck equations on Cantor sets with local fractional derivative. The obtained results give the present method that is very effective and simple for solving the differential equations on Cantor set.